The real-world safety of Ofatumumab: a pharmacovigilance analysis based on the FDA adverse event reporting system - Zhou, Yue; Wu, Yutong; Zhao, Xiao; Xu, Lingxu; Sun, Mingguang; Meng, Zhaoyou (Frontiers in Immunology, 2025)
BackgroundOfatumumab is a humanized monoclonal antibody that targets CD20-positive B cells. It was approved by the FDA in 2020 for the treatment of relapsing multiple sclerosis (RMS) in adult patients, and in 2009 for the treatment of Chronic Lymphocytic Leukemia (CLL). With the escalating clinical application of Ofatumumab, comprehending its safety profile within actual healthcare environments is of considerable importance.MethodsThis study compiled a dataset derived from the FAERS database, which included real-world safety data on Ofatumumab from Q4 2009 to Q2 2024. We applied four distinct methodologies, including ROR, PRR, MGPS, and BCPNN, to perform a disproportionality analysis of adverse events (AEs) associated with Ofatumumab. Furthermore, we utilized the Weibull distribution model to estimate the temporal risk pattern of AEs.ResultsThe investigation incorporated a total of 24,468 case reports pertaining to AEs associated with Ofatumumab. The commonly observed AEs encompass Fatigue, Headache, Chills, Pyrexia, Pain, Nausea, Nasopharyngitis, Vomiting, Urinary tract infection, and Pneumonia. Additionally, we identified potential AEs not specified on the drug label, such as Asthenia, Hypoesthesia, Dizziness, Malaise, Injection site pain, Paresthesia, and Diarrhea.ConclusionsThis investigation has identified several AEs associated with Ofatumumab and revealed previously unacknowledged potential adverse reaction signals. Healthcare providers can refer to these adverse reaction signals to more comprehensively consider the possible conditions that patients may present with during actual clinical practice.